A COMPARATIVE STUDY BETWEEN ONLINE AND FACE-TO-FACE LEARNING METHODS ON STUDENT LEARNING OUTCOMES - Saskia Renata; Debi Handika; Rai Markus Panamuan; Wanty Eka Jayanti (Yayasan Nuraini Ibrahim Mandiri, 2025)
The development of digital technology has had a significant impact on the behavior of the younger generation, one of which is the increasing involvement in online gambling activities. This study aims to examine the impact of online gambling on social interaction and emotional stability of the younger generation. The method used is a quantitative study through data collection techniques using questionnaires, this study aims at children aged 16-26 years who are active or have been involved in online gambling. The results of the study show that involvement in online gambling causes a decrease in the quality of social interaction, such as withdrawing from the social environment, decreasing communication skills, and increasing conflict in interpersonal relationships. In addition, there were disturbances in emotional stability in the form of anxiety, excessive stress, uncontrolled anger, and symptoms of depression. Dependence on online gambling also interferes with cognitive function and decision-making, which has a negative impact on the psychological well-being of the younger generation. Therefore, preventive and curative efforts are needed from various parties, including families, educational institutions, and the government, to reduce the negative impacts of this phenomenon. Keywords: online gambling, social interaction, emotional stability, young generation